Internet-delivered cognitive therapy for PTSD: a development pilot series. Issue 1 (1st December 2016) - Wild, Jennifer; Warnock-Parkes, Emma; Grey, Nick; Stott, Richard; Wiedemann, Milan; Canvin, Lauren; Rankin, Harriet; Shepherd, Emma; Forkert, Ava; Clark, David M.; Ehlers, Anke
Abstract : Background: Randomised controlled trials have established that face-to-face cognitive therapy for posttraumatic stress disorder (CT-PTSD) based on Ehlers and Clark's cognitive model of PTSD is highly effective and feasible with low rates of dropout. Access to evidence-based psychological treatments for PTSD is insufficient. Several studies have shown that therapist-assisted treatment delivery over the Internet is a promising way of improving access to cognitive behavioural therapy interventions. Objective: To develop an Internet version of CT-PTSD that significantly reduces therapist contact time without compromising treatment integrity or retention rates. Methods: We describe the development of an Internet version of CT-PTSD. It implements all the key procedures of face-to-face CT-PTSD, including techniques that focus on the trauma memory, such as memory updating, stimulus discrimination and revisiting the trauma site, as well as restructuring individually relevant appraisals relating to overgeneralisation of danger, guilt, shame or anger, behavioural experiments and planning activities to reclaim quality of life. A cohort of 10 patients meeting DSM-IV criteria for PTSD worked through the programme, with remote guidance from a therapist, and they were assessed at pre- and post-treatment on PTSD outcome, mood, work and social adjustment and process measures. Results: No patients dropped out. Therapists facilitated the treatment with 192 min of contact time per patient, plus 57 min for reviewing the patient's progress and messages. Internet-delivered CT-PTSD was associated with very large improvements on all outcome and process measures, with 80% of patients achieving clinically significant change and remission from PTSD. Conclusions: Internet-delivered cognitive therapy for PTSD (iCT-PTSD) appears to be an acceptable and efficacious treatment. Therapist time was reduced to less than 25% of time in face-to-face CT-PTSD. Randomised controlled trials are required to evaluate systematically the acceptability and efficacy of iCT-PTSD. Highlights of the article: iCT-PTSD was acceptable to patients and associated with very large improvements on PTSD outcome and process measures. iCT-PTSD required substantially less therapist time than CT-PTSD. iCT-PTSD may be associated with changes in employment status. Randomised controlled trials are required to systematically evaluate the acceptability and efficacy of iCT-PTSD.